Pengaruh Intensitas Belajar di Rumah terhadap Hasil Belajar Matematika Siswa Kelas V SDN Gedanganak 03 Ungaran - Munfaidah, Hemi (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2023)
This research was motivated by the lack of maximum learning outcomes in Mathematics and the low intensity of learning at home by fifth grade students at SDN Gedanganak 03 Ungaran. The purpose of this study was to determine whether or not the intensity of studying at home had an effect on the mathematics learning outcomes of fifth grade students at SDN Gedanganak 03 Ungaran. The type of research used is ex post facto quantitative research. The population in this study amounted to 35 students of class V. The sampling technique used saturated sampling because all the populations in this study were used as samples. The variables studied included: the intensity of studying at home and learning outcomes of Mathematics. Data collection techniques using a questionnaire. Then the results of the data obtained were analyzed using a simple linear regression test. Based on the results of the research and after the data was analyzed, there was an effect of the intensity of studying at home on learning outcomes in Mathematics. This is shown by the results of simple linear regression, namely the value of Sign. smaller than 0.05 (0.00 <0.05) or, tcount > ttable (5.279 > 2.035). Then Ha is accepted and H0 is rejected. This means that there is a significant influence between the intensity of studying at home on the mathematics learning outcomes of fifth grade students at SDN Gedanganak 03 Ungaran.Keywords: learning intensity, home, learning outcomes, mathematics